(untitled) (Journal of Enam Medical College, 2012)
Germ cell tumors are malignant (cancerous) or nonmalignant (benign, noncancerous) tumors that are comprised mostly of germ cells, the cells that develop in the embryo and become the cells that make up the reproductive system in male and female. Most ovarian tumors are of germ cell origin. A 5-year-old female child was taken to the Paediatrics department at Tawau General Hospital (TGH), Sabah, Malaysia on 10.4.2005 with gradual distension of abdomen which had been noticed by parents for the last 2 months. As bedside ultrasonography (USG) showed mixed echogenic mass in the lower abdomen, CT scan of abdomen was requested for further delineation. CT scan of abdomen done on 18.4.2005 showed a very large (about 12 × 9 cm) mixed density mass with homogenously enhancing well defined borders in the abdomen extending from the pelvic cavity to the upper abdomen causing significant pressure effect downwards towards urinary bladder and contrast material filled guts outwards and backwards mostly occupying the anterior part of abdominal cavity. The tumor was removed surgically and diagnosed as ovarian teratoma histopathologically. DOI: http://dx.doi.org/10.3329/jemc.v2i2.12846 J Enam Med Col 2012; 2(2): 94-96